Anastrozole-Induced Dermatitis: Report of a Woman with an Anastrozole-Associated Dermatosis and a Review of Aromatase Inhibitor-Related Cutaneous Adverse Events - Yoo Jung Kim; Philip R. Cohen (Adis, Springer Healthcare, 2020)
Abstract Anastrozole is an aromatase inhibitor. Anastrozole competitively inhibits the aromatase enzyme, which synthesizes estrogen. It is used for estrogen receptor-positive breast cancers. A woman with breast cancer and anastrozole-induced dermatitis is described; the cutaneous side effects associated with aromatase inhibitors are also reviewed. Skin-related adverse events associated with aromatase inhibitor use are uncommon and may be delayed in appearance; the time of onset ranges from less than 5 days to 6 months (median 2 months). They present as either vasculitis, erythema nodosum, subacute cutaneous lupus erythematosus, or other dermatoses. Some patients demonstrate cutaneous lesions at either the original site of the breast malignancy or in areas that were previously treated with surgery or radiotherapy. The skin reactions are usually treated with discontinuation of the aromatase inhibitor; topical corticosteroids or oral corticosteroids or both are also used for some patients. Our patient's drug reaction occurred 2 months after starting the anastrozole and improved after a course of oral and topical corticosteroids. She was able to be switched to an alternate aromatase inhibitor without a recurrence of her adverse skin reaction.